The Impact of Organizational Culture and Non-Physical Work Environment on Employee Performance Through Job Satisfaction as an Intervening Variable - Nathania Mega Octavia Silalahi; Novi Fitria Hermiati (Universitas Muhammadiyah Makassar, 2023)
Job satisfaction is very important and plays a role in influencing company branding, if employees feel dissatisfied at work, then employees will also show a negative attitude towards their work. The purpose of this study was to determine how much influence organizational culture and non-physical work environment have on employee performance through job satisfaction as an intervening variable. This research is quantitative and collects data through questionnaires. This study has a population of 100 people and a sample of 80 people. The sampling technique in this study was probability sampling using simple random sampling using the Slovin formula. The data analysis method in this study uses the Partial Least Square program with the help of the SmartPLS software application program to obtain results where Organizational Culture has no influence on Employee Performance, Non-Physical Work Environment has an influence on Employee Performance, Organizational Culture has no influence on Job Satisfaction, Non-Physical Work Environment has an influence on Job Satisfaction, Organizational Culture has no influence on Employee Performance mediated by Job Satisfaction, Non-Physical Work Environment has an influence on Employee Performance mediated by Job Satisfaction.